Strategic alliances and interfirm knowledge transfer - Mowery, David C.; Oxley, Joanne E.; Silverman, Brian S. (Strategic Management Journal, 1996)
Abstract This paper examines interfirm knowledge transfers within strategic alliances. Using a new measure of changes in alliance partners' technological capabilities, based on the citation patterns of their patent portfolios, we analyze changes in the extent to which partner firms' technological resources ‘overlap’ as a result of alliance participation. This measure allows us to test hypotheses from the literature on interfirm knowledge transfer in alliances, with interesting results: we find support for some elements of this ‘received wisdom’—equity arrangements promote greater knowledge transfer, and ‘absorptive capacity’ helps explain the extent of technological capability transfer, at least in some alliances. But the results also suggest limits to the ‘capabilities acquisition’ view of strategic alliances. Consistent with the argument that alliance activity can promote increased specialization, we find that the capabilities of partner firms become more divergent in a substantial subset of alliances.